The Many-faced Phoenix: issues regarding the vitality of the Turkic peoples’ shamanism - Bakhtikireeva Улданай; Temirgazinа Зифа (Turkic Studies Journal, 2022)
The article proposes an interdisciplinary approach to the problem of shamanism, accumulating cultural, sociological, philosophical and linguistic components of this phenomenon unique to human civilization. The term shamanism refers to a combination of various healing, mystical-clairvoyant and predictive practices of shamans (V.I. Kharitonova). The article analyzes the “decline” of shamanism of the peoples of the North and Siberia of the Russian Federation, the cause of which was the loss of the usual way of life, traditional crafts, language and, as a consequence, the conceptual worldview. In the context of the vitality and decline of shamanism, the practices of shamanism of the Turks-highlanders – Karachais, Balkars and Steppe Turks – Kazakhs are studied. The first preserved the rudiments of this phenomenon in some modern practices, rituals, dances and in everyday life. Shamanism of these Turkic peoples and others is characterized by syncretism, “dual faith”, i.e. the combination of pagan, Tengrian traditions and Islamic views. A particularly important role in Kazakh practices is played by faith in the spirits of ancestors – aruaktar. Kazakh shamanism today has transformed mainly into healing practices that are widespread everywhere, which indicates its higher vitality compared to the Karachay and Balkars. Trying to trace the vitality of various ethnic shamanic practices, the authors focused on the primary sources, rather than on their interpretation and criticism, so that the reader could get acquainted with a fairly representative set of opinions of various researchers of shamanism and shamanic practices.